Yield, nitrogen-use efficiency, and distribution of nitrate-nitrogen in the soil profile as influenced by irrigation and fertilizer nitrogen levels under zero-till wheat in the eastern Indo-Gangetic plains of India - Sahoo, Samaresh; Mukhopadhyay, P.; Sinha, A. K.; Bhattacharya, P. M.; Rakesh, S.; Kumar, Rajkishore; Padbhushan, Rajeev; Bijay-Singh,; Parmar, Brajendra; Vishwakarma, Anand; Kumar, Amarendra; Yadav, Brahamdeo Kumar; et al. (Frontiers in Environmental Science, 2022)
Due to introduction of zero-till wheat in the Indo-Gangetic plains (IGP) in India, irrigation and fertilizer nitrogen (N) management needs to be modified from that followed under conventionally tilled fields. A field experiment was conducted to study the effect of irrigation and N levels on yield and N uptake by zero-till wheat, fertilizer N use efficiency and distribution of nitrate-N (NO3-N) in soil profile under zero-till conditions in an acidic alluvial soil of the eastern IGP. The experiment was laid out in a split-plot design with four levels of irrigation as main plots [I0-no irrigation (rainfed), I1-122 mm in one irrigation at 25 day after sowing (DAS), I2-263 mm in two irrigations at 25 and 40 DAS, and I3-386 mm in three irrigations at 25, 40 and 55 DAS] and four N levels [0 (N0), 60 (N1), 120 (N2) and 150 (N3) kg N ha-1] as subplots. Grain and straw yield were significantly higher at the irrigation level-I2 and 120 kg N ha-1(N2) over the control (I0 and N0) and were at par with the highest applied levels of irrigation and N (I3 and N3). Nitrogen uptake by wheat followed the trend similar to yield for irrigation levels; however it increased significantly up to 150 kg N ha-1.After the harvest of wheat crop more NO3-N was observed in the 60-90 cm subsurface soil layerthan in the surface 0-15 cm and or 15-30 cm and 30-60 cm subsurface soil layers. The highest NO3-N concentration was recorded in the treatment I2N2. Accumulation of NO3-N in the soil increased up to irrigation levels I2 and with increasing doses of fertilizer N application. Combined applications of irrigation and N had positive and significant influence on agronomic efficiency and apparent N recovery but no significant effect on PE. This study suggests that that appropriate combination of irrigation and N levels in zero-till wheat can lead not only to high yield levels and N use efficiency but also adequately control NO3-N leaching under acidic alluvial soils in the eastern IGP.